Comparison Study of Operation Characteristics of AFCI Products - Jae, Ra, Woong-; Sung, Kong, Ha- (International Journal of Membrane Science and Technology, 2023)
It is well known that about 80% of electric fire occurs by arc fault. The arc fault can be generated in loose wire connection or damaged wire, outlets, appliances, extension cords, etc. To mitigate the electric fire, US mandated to use Arc Fault Circuit Interrupters (AFCI) since 2002. Before AFCI has been developed, Ground Fault Circuit Interrupters (GFCI) were used for prevention of electric shock accident but GFCIs are not able to detect arc fault that is main cause of electric fire. After AFCI requirement of US established, Canada, Europe, New Zealand also adopted the AFCI as mandatory. It is a worldwide trend to mandate AFCI in their countries. We are living in the era of changing from GFCIs to AFCIs. As the demand for AFCIs increases, many studies regarding development of AFCI products and technologies have been conducted but comparison study of operation characteristics of AFCI has not been done yet, thus in this paper we are going to conduct series of arc experiment with several AFCI products and compare their performance.